Risk factors for anesthesia-associated postoperative capillary leakage after thoracoscopic surgery in neonates: A single-center observational study - Liu, Heqi; Wang, Fang; Zhang, Jianmin; Gao, Zhengzheng (Frontiers in Pediatrics, 2023)
Background Thoracoscopy is considered the surgical method of choice for addressing a wide range of conditions in neonates. However, there is a lack of experience in anesthesia management for this procedure. On reviewing the newborns who had undergone thoracoscopic surgery at our medical center, some had developed edema after surgery. After excluding other etiologies, these neonates were diagnosed with capillary leakage secondary to thoracoscopy. Aims This study aimed to identify the potential risk factors for capillary leakage secondary to thoracoscopy in neonates and to provide reference information for optimal anesthesia management. Methods This single-center, retrospective, observational study examined neonates who had undergone thoracoscopic surgery between January 1, 2018 and September 31, 2021. Their electronic medical records of were analyzed for demographic and clinical characteristics associated with anesthesia, and postoperative capillary leakage occurring within 24 and 48 hours of surgery was assessed based on medical records. Results A total of 56 neonates that underwent thoracoscopic surgery were included in this study. Postoperative capillary leakage within 24 hours was diagnosed in 14 neonates (25%). The partial pressure of carbon dioxide was an independent factor influencing the occurrence of postoperative edema within 24 hours (P=0.021). Overall, 21 cases (37.5%) were diagnosed as postoperative capillary leakage within 48 hours, and age was an independent factor influencing the occurrence of postoperative edema within 48 hours (P=0.027). Conclusions According to our findings, we concluded that preventing the elevation of the partial pressure of carbon dioxide may reduce the occurrence of secondary capillary leakage within 24 hours after thoracoscopic surgery, and that older newborns are less likely to have secondary capillary leakage within 48 hours after thoracoscopic surgery. Our findings provide evidence that directly informs anesthesia management for thoracoscopic surgery in neonates.